Implementation of the Information Motivation Behavior Skill Model on Cadre's Performance in Surakarta: A Structural Equation Model - Chelsy Sumardi Saputri; Argyo Demartoto; Bhisma Murti (Journal of Health Promotion and Behavior, 2024)
Background: Integrated service post cadres are individual volunteers at the community level who are selected by residents based on their ability, integrity, loyalty and commitment to improving community health and playing a role in developing strategies to overcome stunting. This research aims to determine whether there is an effect of implementing the Information-Motivation-Behavior Skill Model on the performance of Integrated services post cadres. Subjects and Method: This was a cross-sectional study conducted in Surakarta, Central Java, form November to December 2023. A sample of 210 integrated services post cadres was selected using stratified random sampling. 25 integrated service posts in 3 community health centers The data were collected using a structural equation modeling (SEM). Results: Performance was positively and significantly influenced by behavioral skill (b= 0.26; 95% CI= 0.13 to 0.38; p< 0.001), information (b= 0.16; 95% CI= 0.03 to 0.28; p= 0.014), and motivation (b= 0.18; 95% CI= 0.05 to 0.32; p= 0.008). Goodness of fit of SEM model indicated fit (p= 0.190; RMSEA= 0.037; CFI= 0.99, TLI= 0.98, SRMR= 0.03; CD= 0.92). Conclusion: The Information-Motivation-Behavioral Skill Model can be used to predict work performance of integrated health post cadres. Performance is positively and significantly influenced by behavioral skill, information, and motivation.